History of development of the system and activity-based approach to education - Holubnycha, Liudmyla; Zelenska, Liudmyla (Національний технічний університет "Харківський політехнічний інститут", 2022)
The article reveals the meaning of the notions "activity" and "system" both in general and pedagogical science context as the integration components of the system and activity-based approach to education. The purpose of the article is to characterize the concept of the system and activity-based approach and describe its development applied to the educational process. Emphasis is placed on the history of the development of the system and activity-based approach. The results of the investigation made it possible to conclude reveal that the idea to combine system-based and activity-based approaches does not belong to one scientist. It appears in a number of works of philosophers and psychologists of the first part of the 20th century. Considering the issues of teaching and raising a child gave a substantial impulse to the development of this idea in the 1960s-1990s. Nowadays the studied methodological approach to educational process complements other ones.

У статті розкрито значення понять "діяльність" і "система" як у загальному, так і в педагогічно-науковому контексті як інтеграційних компонентів системно-діяльнісного підходу до навчання. Мета статті – охарактеризувати поняття системно-діяльнісного підходу та описати його розвиток у застосуванні до навчального процесу. Акцент зроблено на історії розвитку системно-діяльнісного підходу. Результати дослідження дозволили зробити висновок, що ідея поєднання системного та діяльнісного підходів належить не одному вченому, а зустрічається в ряді робіт філософів і психологів першої половини ХХ ст. Розгляд питань навчання та виховання дитини дав істотний поштовх розвитку цієї ідеї в 1960-1990-х роках. Нині досліджуваний методичний підхід до освітнього процесу доповнює інші методологічні підходи.
Історія розвитку системно-діяльнісного підхіду до навчання
Keywords: methodological approach; activity; system; development of the system and activity-based approach; education; system-based approach; education; system-based approach; activity-based approach; методологічний підхід; діяльність; система; розвиток системнодіяльнісного підходу; освіта; системний підхід; діяльнісний підхід